Customer Satisfactions Based on Service Quality for VVIV Inpatient Patient of PMI Bogor Hospital - Fadly, Mohammad Rizky; Gemina, Dwi; Gunawan, Rachmat (MultiTech Publisher, 2024)
The success of health development plays an important role in improving the quality of human resources in Indonesia. The goal of health development itself can be achieved through various forms of implementing health efforts in a comprehensive, tiered and integrated manner. This research aims to analyze service quality on customer satisfaction simultaneously and partially for VVIP patients at PMI Bogor Hospital. The sample size was 100 respondentsnon-probability sampling technique. The questionnaire was tested using validity tests, reliability tests and also classical assumption tests. The test is valid, reliable, has classic assumptions and can be used for multiple linear regression data. The analytical method used in this research is a descriptive and verification method with a quantitative approach. The results of the research show that there is a positive and significant simultaneous and partial influence of service quality on consumer satisfaction.